Magical and religious beliefs in Medicine in Pre-Hispanic America - Frisancho Velarde, Óscar (2012)
The origins of medicine in pre-Hispanic South America are still evident in the magic and religious cosmic vision that influences the beliefs of many native South American with respect to health and disease and their therapy approaches. This magical-religious approach for health and disease has been widely spread in North, Central and South America cultures.